The Effect of Bonus Plan, Political Cost and Earning Management toward Social and Environment Disclosure Quality - Gabriella Ebri Rosani; Setyarini Santosa, S.E., MAFIS, Ak. (President University Press, 2020)
This research examines whether bonus plan, political cost, and earning management have influence to the social and environment disclosure quality or corporate social responsibility This research is important due to the increasing level of public awareness to the social and environmental disclosures that in turn, it can be used as part of the corporate strategy to attract the market as well as the stakeholder. There are 45 companies used as samples and are taken from the manufacturing companies listed in Indonesia Stock Exchange for the period of 2013-2017. Using multiple linear regression, the finding from this research shows that both earning management and political cost have positive significant effect towards social and environment disclosure quality, while bonus plan has insignificant effect towards social and environment disclosure quality.